Changing the decision context to enable social learning for climate adaptation - Colloff, M. J.; Gorddard, R.; Munera-Roldán, C.; Locatelli, B.; Lavorel, S.; Allain, S.; Bruley, E.; Butler, J. R. A.; Dubo, T.; Enokenwa Baa, Ojongetakah; González-García, A.; Lécuyer, L.; et al. (Wiley, 2025)
1. Successful adaptation often involves changes to the decision context to enable new ways of thinking and acting on climate change. Using 16 adaptation initiatives the authors were engaged with, we analysed how and why decision contexts changed to identify ways to improve adaptation as a process of collective deliberation and social learning.